2015
DOI: 10.1039/c5sc00708a
|View full text |Cite
|
Sign up to set email alerts
|

Shape and composition control of Bi19S27(Br3−x,Ix) alloyed nanowires: the role of metal ions

Abstract: Highly uniform single-crystalline Bi19S27(Br3–x,Ix) alloyed nanowires (NWs) (0 ≤ x ≤ 3) were achieved for the first time. The NWs show a composition-independent band gap and have great application potential in optoelectronic devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 59 publications
1
34
0
Order By: Relevance
“…Since bismuth chalcogenides and bismuth chalcogenide halides are of interest as photovoltaic materials (exemplified by recent work on “Bi 19 Br 3 S 27 ” nanowires as photocatalysts and BiSI 1‑x Br x photovoltaic studies), UV–vis/near-IR diffuse reflectance measurements were carried out to investigate the optical properties of flux-grown Bi 13 S 18 I 2 . As shown in Figure , Bi 2 S 3 has an absorption edge of 1.29 eV, which agrees with reported values of 1.24–1.35 eV. , Flux-grown BiSI has an absorption edge of 1.55 eV, also in agreement with the reported values of 1.57–1.59 eV. ,, Optical properties of bulk “Bi 19 S 27 I 3 ” have not been reported.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Since bismuth chalcogenides and bismuth chalcogenide halides are of interest as photovoltaic materials (exemplified by recent work on “Bi 19 Br 3 S 27 ” nanowires as photocatalysts and BiSI 1‑x Br x photovoltaic studies), UV–vis/near-IR diffuse reflectance measurements were carried out to investigate the optical properties of flux-grown Bi 13 S 18 I 2 . As shown in Figure , Bi 2 S 3 has an absorption edge of 1.29 eV, which agrees with reported values of 1.24–1.35 eV. , Flux-grown BiSI has an absorption edge of 1.55 eV, also in agreement with the reported values of 1.57–1.59 eV. ,, Optical properties of bulk “Bi 19 S 27 I 3 ” have not been reported.…”
Section: Results and Discussionmentioning
confidence: 99%
“…To overcome these limitations, liquid‐phase synthetic approaches have been introduced with the aim of enabling the post‐synthesis deposition of the bismuth chalcohalides onto substrates [24–26] . Recently, the issue of processability has been further addressed by colloidal synthetic methods yielding solvent dispersible nanocrystals of Bi 13 S 18 I 2 [27, 28] . However, there are no reports to date of the colloidal synthesis of BiSI or related nanomaterials (such as BiSBr or BiSeBr), despite them being suggested as potentially efficient, defect tolerant photoactive materials for solar energy conversion purposes.…”
Section: Introductionmentioning
confidence: 99%
“…With the help of selective surface binding ligands, impurity elements are shown to be selectively attracted to the surface, inhibiting the growth and hence enabling the formation of nanoparticles with certain facets. , It has been theoretically shown that adsorption on certain surfaces is energetically more favorable for certain impurity elements. , Once the impurity is adsorbed, the growth is interrupted and finally hindered from that surface. With this approach, nanoparticles with remarkable control over morphology and size have been designed and synthesized. …”
Section: Introductionmentioning
confidence: 99%